Pengaruh Teknologi Informasi untuk Meningkatkan Pelayanan dalam Proses Belajar Mengajar - Sugandi, Lianna (Bina Nusantara University, 2014)
In the current age of globalization there has been a new paradigm shift in the business world and has given rise to new demands on higher education institutions, it is caused by the development of competition which is characterized by interdependence of economic change and the development of information technology as the backbone of the process the business of a company. Competition in the world of college education today is increasingly heavy and important. Each college is required to have an added value in order to win the competition with other universities. The increasing public demand for formal education, especially higher education, makes college as a strategic sector that is expected to produce quality human resources. College success is largely determined by the quality of service provided, which can be identified service quality through customer satisfaction in this case are students and faculty. In order to improve customer satisfaction, to be able to compete in the era of globalization and alsoto provide bigger profit, then every university is doing a research to determine the factors that influence the information systems services to customer satisfaction.